Sistem Absensi Perkuliahan Berbasis Website Di Kampus Politeknik Manufaktur Negeri Bangka Belitung - Sahputra, Reza; Nasrul Hadi, Alfiqri; Josi, Ahmad; Rindri, Yang Agita (Jurnal Inovasi Teknologi Terapan, 2025)
The State Manufacturing Polytechnic of Bangka Belitung (Polman Babel) faces challenges in managing student and lecturer attendance, especially related to late attendance. This study develops a website-based attendance system to improve the efficiency and accuracy of attendance recording. Using the Waterfall Model method, this system is desained to make it easier for lecturers to record attendance, lateness, and compensation time, and is equipped with a compensation recording feature. The results of the study show that this system can reduce errors in recording and accelerate data recapitulation, with a total user trial skor reaching 72.5%, so it is declared suitable for use. This system also maintains the security of student data and privacy through the appropriate login feature.